2014
DOI: 10.1007/s00441-014-1944-3
|View full text |Cite
|
Sign up to set email alerts
|

TNAP activity is localized at critical sites of retinal neurotransmission across various vertebrate species

Abstract: Evidence is emerging with regard to the role of tissue non-specific alkaline phosphatase (TNAP) in neural functions. As an ectophosphatase, this enzyme might influence neural activity and synaptic transmission in diverse ways. The localization of the enzyme in known neural circuits, such as the retina, might significantly advance an understanding of its role in normal and pathological functioning. However, the presence of TNAP in the retina is scarcely investigated. Our multispecies comparative study (zebrafis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…The lack of responsiveness to levamisole leads to the assumption that those organs express an intestinal (alpi.1 or alpi.2) instead of the tissue-nonspecific isoform of the AP (alpl). Additionally, the highest alpl expression levels along with strong AP-activity can be observed in the eyes, more precisely in the lens and the retina, which seems to be conserved between different vertebrate species and is in line with previously published literature 15 . However, no specific symptoms concerning the visual performance of HPP patients have been described so far and the exact role of TNAP/Tnap in the visual system and potential compensatory mechanisms remain to be unraveled in future experiments.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The lack of responsiveness to levamisole leads to the assumption that those organs express an intestinal (alpi.1 or alpi.2) instead of the tissue-nonspecific isoform of the AP (alpl). Additionally, the highest alpl expression levels along with strong AP-activity can be observed in the eyes, more precisely in the lens and the retina, which seems to be conserved between different vertebrate species and is in line with previously published literature 15 . However, no specific symptoms concerning the visual performance of HPP patients have been described so far and the exact role of TNAP/Tnap in the visual system and potential compensatory mechanisms remain to be unraveled in future experiments.…”
Section: Discussionsupporting
confidence: 91%
“… Tissue Primates Mouse Zebrafish Blood vessels + + + Retina + + + Forebrain Diencephalon (hypothalamus, thalamus) n.a + + Telencephalon (amygdala, olfactory bulb, cortex, hippocampus, septum, pallium) + + + Olfactory bulb n.a + n.a Midbrain Ventricular zones (e.g. DiV and TeV in the midbrain) + + + Septum n.a + + Hindbrain Medulla oblongata, metencephalon n.a + + References 6 , 13 15 , 59 62 15 , 16 , 18 , 57 , 60 , 63 , 64 MGI database: 87,983 15 own data n.a. : not available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of interest that the high activity of TNAP in the cortex coincides with the peak of synaptogenesis [55,56] , suggesting a functional involvement of TNAP in synapse formation and maturation. Recent studies demonstrated the presence of TNAP in the retina of several vertebral species, including humans, suggesting a role in retinal neurotransmission [57] . While the precise biological functions of TNAP at these CNS sites remain to be further elucidated, emerging evidence suggests that TNAP may act through metabolic pathways additional to hydrolyzing extracellular nucleotides.…”
Section: Tnap and Synaptic Functionmentioning
confidence: 99%
“…Kantor et al describe TNAP activity in the eye localized to vessels of the retina, the photoreceptor layer, and mostly in the outer and inner plexiform layers within many species [182]. TNAP/Tnap is present in the sublayers of the inner plexiform layer, especially in rats and zebrafish, respectively [182,183]. Nevertheless, to the best of our knowledge, no impairment concerning vision ability has been reported in the context of HPP patients so far, which may suggest the presence of a compensatory mechanism in the human eyes.…”
Section: Visual Perceptionmentioning
confidence: 99%